2022
DOI: 10.5115/acb.21.177
|View full text |Cite
|
Sign up to set email alerts
|

A study on the correlation between spleen volume estimated via cavalieri principle on computed tomography images with basic hemogram and biochemical blood parameters

Abstract: Considering its hematological and immunological functions, spleen is a very important organ. A change occurs in its size as the spleen performs these functions. This study aims to examine the possible relationships between spleen volume and the basic hemogram and biochemical parameters in serum. Multidetector computed tomography images and basic hemogram and biochemical parameters of 74 adult individuals, 34 male and 40 female, who were found to be healthy, were used in the study. Spleen volume was estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Similar to our findings, a previous study conducted in small group of healthy individuals also found positive associations of spleen volume with hemoglobin and RBC as well as inverse associations of spleen volume with platelet count and lymphocytes percentage ( 6 ). A comparable result was also obtained from a small group of patients where an inverse association of spleen volume with WBC was observed ( 8 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to our findings, a previous study conducted in small group of healthy individuals also found positive associations of spleen volume with hemoglobin and RBC as well as inverse associations of spleen volume with platelet count and lymphocytes percentage ( 6 ). A comparable result was also obtained from a small group of patients where an inverse association of spleen volume with WBC was observed ( 8 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, compared to the aforementioned studies, which were conducted on small groups of patients and healthy individuals or using experimental animal models, we used a large sample size of individuals selected from a general population. Although one of the previous studies used CT for spleen volume assessment ( 6 ), we used MRI for spleen volume measurement, which is a more accurate and sensitive marker than CT or ultrasonography ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spleen is considered a critical immune organ because it helps regulate red blood cells and the immune system [ 14 ]. In this organ, old red blood cells are removed, and the protein portion of hemoglobin is metabolized to maintain the homeostasis of the body [ 15 ]. The spleen consists of two main sections: white pulp (25%) and red pulp (76–79%).…”
Section: Discussionmentioning
confidence: 99%
“…The spleen, derived from mesenchymal tissue, is the largest lymphatic organ found in all vertebrates [ 1 ]. The spleen (the multipurpose internal organ) has very important physiological roles in regard to red blood cells, storage of blood, the centre of the blood defence system, the immune system, as well as the formation of lymphocytes and eliminating senescent erythrocyte cells [ 2 , 3 , 4 ]. Moreover, the spleen controls physiologically essential processes, e.g., metabolism of metals, albuminoids, and, what is recently gaining increasing attention, the metabolism of lipids.…”
Section: Introductionmentioning
confidence: 99%